ABOUT THE QUALITIES OF KHOJA ABDULKHOLIQ GIJDUVANI'S STUDENTS (Scientific journal of the Fergana State University, 2024)
In this article, the great teachings of Khoja Abdulkhaliq Gijduvani about the qualities of a master-disciple are presented, and the order of the master-disciple relationship, the qualities of a master, and the fact that the role of a master is incomparable in a student's rightful place in life are analyzed philosophically. It is explained through life examples that a student who patiently follows the teacher's instructions can spend his life and time usefully and become a valuable person and an educated person for the society. In turn, it is explained that since the body and soul of the young generation are entrusted to the beloved teacher, teachers should also take such a huge responsibility seriously. It is reflected in this article that Alloma's teachings on valuing teacher-student relationships are an important lesson that should be learned by the future generation.